Designing an upper body resistance training - Chandler, B. (Coaching and Sport Science Review, 2020)
The purpose of this article is to summarize research on the effects of CKC and OKC upper body resistance training on serve velocity. Practical applications of this research are discussed and examples of how these exercises can be implemented into a tennis player`s training program are provided.